Fostering Employee Innovation through Authentic Leadership: The Mediating Role of Technology Diversity in the Telecom Industry of Pakistan - Awab, Ahmad; Mohd Zainal Munshid, Harun; Muhammad Farhan, Jalil (MDRI, 2025)
This study investigates the relationship between authentic leadership and employees’ innovation, with a particular focus on the mediating role of technological diversity in Pakistan’s telecommunication sector. Drawing upon authentic leadership theory, the research conceptualizes leadership through four key dimensions: self-awareness, relational transparency, balanced processing, and internalized moral perspective. A quantitative, cross-sectional research design was adopted, and data were collected from 379 executive-level employees across four major telecommunication companies—Jazz, Telenor, Ufone, and Zong—using proportionate stratified random sampling. Structural Equation Modelling (SEM) using AMOS was employed for data analysis. The findings confirm that authentic leadership positively influences employees’ innovation and that technological diversity partially mediates this relationship. The results highlight the strategic importance of integrating ethical leadership with technological capability to foster innovation in fast-evolving and competitive industries. The study contributes both theoretically and practically by emphasizing the role of leadership style and technological resources in driving innovation performance in emerging market contexts.